Glyphosate efficacy on sourgrass biotypes with suspected resistance collected in GR-crop fields - Silveira, Hellen Martins da; Langaro, Ana Claudia; la Cruz, Ricardo Alcántara-de; Sediyama, Tocio; Silva, Antonio Alberto (Acta Scientiarum. Agronomy, 2018)
In Brazil, infestations of crop areas with glyphosate-resistant (GR) sourgrass (Digitaria insularis (L.) Fedde) biotypes has risen significantly, increasing crop production costs. Glyphosate efficacy on three biotypes (GO, BA and MT) of sourgrass with suspected resistance was evaluated. A susceptible biotype (MG) was used as the control. The results confirmed that the MG and GO biotypes were susceptible to glyphosate (control > 90%). The MG biotype exhibited growth reduction and mortality by 50% (GR50 and LD50, respectively) with mean glyphosate doses of 243.7 and 431.6 g ae ha-1. The resistance index of the biotypes with suspected resistance ranged from 2.8 to 6.1 in relation to GR50 and between 1.4 to 26.7 in relation to LD50. The glyphosate susceptibility ranking of the sourgrass biotypes was MG < GO < MT < BA. The MT and BA biotypes demonstrated high glyphosate resistance levels, and the GO biotype had a high potential to develop resistance. Farmers should avoid the application of glyphosate overdoses to minimize the selection pressure on weeds.